Nutrient requirements of growing Angora rabbits - SINGH, GEETANJALI; SHARMA, K S; KUMARI, MEENA; KATOCH, B S (The Indian Journal of Animal Sciences, 2013)
Angora rabbit kits (25), 40-day-old were equally distributed on almost equal average body weight basis into 5 groups and allotted to 5 test diet treatments with 5 kits in each treatment and fed up to 140 days of age. Out of 5 test diets fed for 100 days, 02 test diet CP- 17.25%, lysine (0.69%, threonine-0.63%, methionine + cystine-0.69% and DE-2875 Kcals/kg)showed the best growth performance by showing significantly highest (P<0.05) lives weight gain coupled with efficient feed conversion ratio, zero kit mortality, highest wood production per kg body weight, highest pure fibre percentage and also highest digestibility of various nutrients. However, Ds test diet (CP-10.50%, lysine-0.42%, threonine-0.39%, methionine + cystine-0.39% and DE-1750 Kcallkg) showed 100% mortality within 2 fortnights of feeding trial because of chronically inadequate supply of critical nutrients to meet the bare minimum maintenance needs of growing kits. This study has shown that the growing Angora kits need 17.25% CP, 0.69% lysine, 0.63% threonine, 0.69% sulphur containing amino acids and 2875 Kcals/kg of digestible energy for optimum growth during summer under mid hills conditions of Himachal Pradesh.